Demographic analysis of education for sustainable development among higher education institution students in China - Chen, Di; Prabowo, Thoriq Tri; Poungsuk, Pakkapong (My University, 2025)
Purpose – The purpose of this study is to examine the impact of demographic factors on Education for Sustainable Development (ESD), and the diverse perspectives held by students at different higher education institutions (HEIs) in China. This study aims to advance ESD and contribute to achieving the 2030 Sustainable Development Goals with five years remaining. Design/methodology/approach – This study examines 706 students from five HEIs using a convergent mixed-methods approach. A Likert scale assessed ESD levels and demographics, with t-tests and ANOVA analysing demographic influences. Thematic analysis of open-ended responses explored students’ ESD perspectives. Findings – HEI students in China show high awareness of ESD. Significant differences were found based on age, gender, institution, academic level, major and GPA, whereas education level and residence showed no impact. A gap remains between ESD awareness and actual behaviour. Research limitations/implications – Future research should explore more demographic variables, include diverse education levels and expand globally. Multi-source questionnaires are recommended for greater depth and comprehensiveness. Practical implications – The study highlights the need to bridge the awareness–behaviour gap through experiential learning, curriculum integration, faculty training and supportive policies. Originality/value – This study is the first to explore the impact of demographics on HEI students’ ESD perspectives in China, using qualitative questions to enrich quantitative findings.
Keywords: China; Demographic; Education for sustainable development; Higher education institutions; Sustainable Development Goals